2021
DOI: 10.3390/nu13020535
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Probiotic Fermented Soy Product Reduces Total and LDL Cholesterol: A Randomized Controlled Crossover Trial

Abstract: Traditional Asian fermented soy food products are associated with reduced cardiovascular disease risk in prospective studies, but few randomized controlled trials have been conducted in at-risk populations. The aim of this study was to investigate the effect of a commercial non-probiotic fermented soy product on blood lipids in adults with cardiovascular risk biomarkers. In a randomized, crossover, intervention study, 27 men and women (aged 29–75 y) exhibiting at least two risk factors, consumed two packets (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 56 publications
(72 reference statements)
1
19
0
Order By: Relevance
“…Meta-analyses of red yeast rice identified significant improvements in LDL-C, TC and TG compared to placebo in dyslipidaemic patients. [36,37,95] Our review also found that some lactofermented foods, [53,63,76] jangs, [67,72,74] tempeh, [58][59][60] brown rice lees [64] and fermented soy powder [69] significantly improved lipid parameters compared to controls.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Meta-analyses of red yeast rice identified significant improvements in LDL-C, TC and TG compared to placebo in dyslipidaemic patients. [36,37,95] Our review also found that some lactofermented foods, [53,63,76] jangs, [67,72,74] tempeh, [58][59][60] brown rice lees [64] and fermented soy powder [69] significantly improved lipid parameters compared to controls.…”
Section: Discussionmentioning
confidence: 58%
“…Notably, 21 out of 26 included studies were conducted in East Asian populations (South Korea, Japan, Indonesia) with one from Western Asia [63] (Iran) using traditional BFFs from these regions, which reflects the importance of these products in their diets. The other studies from Italy, [76] the USA, [69] Iran [75] and Mauritius [61] used nontraditional fermented interventions. East Asians may be at higher risk of poor cardiometabolic outcomes at a lower BMI than Caucasians.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations